Study on Wire Arc Additive Manufacturing Geometric Properties Using Simulation - Khairol Afandi, Aniq Harith; Ibrahim, Mohd Halim Irwan; Mohd Ghazali, Sarah Nadiah (Research Progress in Mechanical and Manufacturing Engineering, 2025)
In Wire Arc Additive Manufacturing, controlling residual stress and keeping constant bead geometry during fabrication is one of the major challenges; it poses limitations to the quality and mechanical properties of its final components. Due to insufficiently optimized heat source parameters, unpredictable thermal distributions and stress formations are produced in WAAM. In this study, A numerical simulation model is developed using finite element analysis. WAAM parameters are optimized based on the Taguchi method to enhance the bead geometry and mechanical properties of WAAM products. WAAM parameters were optimized, voltage and travel speed keeping current and wire feed speed constant. Optimal parameters of 13V and 5 m/min were identified, and the model was developed using a numerical simulation model built with Simufact Welding and optimized through the Taguchi method using an L9 orthogonal array. Single-bead validation produced a 6.0 mm bead width and 4mm bead height with uniform hardness distribution. In comparison, a 10-layer WAAM process gave a final bead width of 9 mm through experimental, 2.27 mm maximum displacement, and equivalent stress of 1.44 Mpa to 274.45 Mpa through simulation The results from this work show that the optimized parameters are satisfactory, and WAAM is a feasible method to produce high-quality components with enhanced accuracy and improved structural integrity.